2022
DOI: 10.3390/foods11142010
|View full text |Cite
|
Sign up to set email alerts
|

International Spread of Tet(X4)-Producing Escherichia coli Isolates

Abstract: Tigecycline resistance in bacteria has become a significant threat to food safety and public health, where the development of which is attributed to plasmid-mediated tet(X4) genes. In this study, the genomes of 613 tet(X4)-producing Escherichia coli (E. coli) isolates, available from public databases, are evaluated to determine their international prevalence and molecular characterization. These E. coli isolates have been disseminated in 12 countries across Asia and Europe. It was found that pigs and their pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It has been found that the IS CR2 element is frequent adjacent to tet (X4) or other tet (X) variants, which suggests IS CR2 is more likely to participate in spread of tet (X) variants ( Wang L. et al, 2019 ; Liu et al, 2020 ; Fu et al, 2021 ). In a conserved genetic environment and uncertain transferability among different bacteria, the co-action of IS CR2 and IS 26 may be the main driving forces for the widespread of tet (X4; Dai et al, 2022 ; Zhang et al, 2022 ).…”
Section: Origin and Spread Of Tet (X4)mentioning
confidence: 99%
“…It has been found that the IS CR2 element is frequent adjacent to tet (X4) or other tet (X) variants, which suggests IS CR2 is more likely to participate in spread of tet (X) variants ( Wang L. et al, 2019 ; Liu et al, 2020 ; Fu et al, 2021 ). In a conserved genetic environment and uncertain transferability among different bacteria, the co-action of IS CR2 and IS 26 may be the main driving forces for the widespread of tet (X4; Dai et al, 2022 ; Zhang et al, 2022 ).…”
Section: Origin and Spread Of Tet (X4)mentioning
confidence: 99%
“…Colistin, carbapenems and tigecycline are considered last-resort antibiotics for defense against MDR bacterial infections ( Tang et al, 2021 ). However, these antibiotics become less effective because their respective predominant resistance genes, mcr , bla NDM and tet(X) , emerge and spread in animals, food and humans ( Singh et al, 2018 ; Zhong et al, 2019 ; Anyanwu et al, 2022 ; Lu et al, 2022 ; Zhang et al, 2022 ). Among these last-resort antibiotics, colistin was heavily used in food-producing animal industries in China for a long period of time until it was banned as a growth promoter in 2017 ( Walsh and Wu, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among the currently available antibiotics, carbapenems, colistin as well as tigecycline are last-resort antibiotics for managing MDR bacterial infections, especially those caused by Enterobacteriaceae ( Tang et al, 2021 ). Unfortunately, the worrying emergence of the predominantly plasmid-borne colistin resistance gene mcr-1 , carbapenem resistance gene bla NDM-1 as well as tigecycline resistance gene tet(X4) in Enterobacteriaceae pathogens from different sources, such as animals, food and humans, has increasingly been reported in different continents ( Singh et al, 2018 ; Zhong et al, 2019 ; Anyanwu et al, 2022 ; Lu et al, 2022 ; Zhang et al, 2022 ). Additionally, tet(X) genes have regularly been reported to coexist with bla NDM-1 and/or mcr-1 genes ( Chen et al, 2019 ; Sun C. et al, 2019 ), and such plasmid-borne antibiotic resistance genes (ARGs) are capable of transferring between epidemic strains of Enterobacteriaceae ( Leshaba et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the identified tet (X) variants that can degrade tigecycline, tet (X4) is recognized as a highly prevalent plasmid-borne variant that exhibits high enzymatic activity and can mediate high resistance to tigecycline (16–32 mg/mL) (He et al 2019 ). To date, tet (X4)-positive strains have been identified in animals (Wang et al 2022a , b ), foods (Sun et al 2021 ), the environment (Cui et al 2020 ), and humans (Cui et al 2022 ; Zhang et al 2022a , b ). Gradually, these strains are increasingly being reported worldwide.…”
Section: Introductionmentioning
confidence: 99%